Construction of The Iftār Tradition In Sergang Village, Sumenep Regency: A Study of Living Hadith - Moh. Isbat Alfan Ghoffari; Abdul Mukit (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The author's research aims to explain the construction of the Ifthār tradition in Sergang Village and the reception of hadiths that underlie the emergence of the Ifthār tradition, as well as other hadiths related to the Ifthār tradition. The research method to be employed is field research, conducted by directly interviewing practitioners (insiders), the general public (outsiders), and community leaders in order to achieve comprehensive research. The research will utilize the theory proposed by Peter L. Berger, using the triad dialectic theory, namely: externalization, objectification, and internalization. The results of the research show that the transmission of the Ifthār tradition has been ongoing for over a century, starting from the third caretaker of Raudlatus Syabab Islamic Boarding School, K.H. Syarqowi. There are two main hadiths that serve as the foundation for this tradition, namely the hadith about Ifthār and the hadith about the virtue of giving charity. Initially, there were no pre-Ifthār rituals among the villagers in Sergang Village. However, over time, the alumni of Pesantren Pajung, who are scattered in various regions, began organizing Ifthār in their own areas, adding several pre-Ifthār rituals. As for the transformation of the hadiths in the Ifthār tradition in Sergang Village, it has undergone five periods, influenced by influential figures from the past until the present era